A Comparison of Plyometric and Jump Rope Training Programs for Improving Punching Performance in Junior Amateur Boxers - Chottidao, Monchai; Kuo, Chia-Hua; Tsai, Shiow-Chwen; Hwang, Ing-Shiou; Lin, Jiu-Jenq; Tsai, Yung-Shen (Frontiers in Bioengineering and Biotechnology, 2022)
Improving lower extremity sports performance may contribute to punching performance in boxers. We compared the effects of two typical boxing routines for developing lower extremity sports performance and subsequent punching performance. A total of 24 high school amateur boxers were separated into two groups to receive an 8-week plyometric or jump rope training program. Each training program was performed for 30 min on 3 days/week. Lower extremity sports performance in countermovement jump (leg stiffness, jump power, and rate of force development) and jab-cross punching performance (punch velocity, punch force, reaction time, movement time, and ground reaction force) were assessed at pre-and post-training. The data were analyzed using a two-way mixed-design analysis of variance (ANOVA) (group x time). Both training programs improved the rate of force development in countermovement jump, the reaction time of punch, the peak ground reaction force of the rear leg during the jab punch, and the velocity of the jab punch. There were no group differences and interaction effects in all variables analyzed in this study. It is concluded that performing an 8-week plyometric or jump rope training program can improve lower extremity sports performance that may contribute to punching performance in junior amateur boxers.